1986
DOI: 10.1523/jneurosci.06-02-00563.1986
|View full text |Cite
|
Sign up to set email alerts
|

Long-term enhancement of hippocampal synaptic transmission and the acquisition of spatial information

Abstract: The hypothesis that memories are stored as a specific distribution of strengths in a population of modifiable synapses was examined by the bilateral induction of long-term enhancement in synapses of the main afferent fiber system to the hippocampal formation in rats. Brief, high-frequency activation of the perforant pathway in chronically prepared animals resulted in a persistent increase in the field EPSP and population spike, measured extracellularly in fascia dentata. This treatment resulted in a profound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
170
4

Year Published

1989
1989
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(194 citation statements)
references
References 35 publications
18
170
4
Order By: Relevance
“…LTP induction has also been shown to have effects on spatial learning. Several groups have shown that when the perforant pathdentate synapses are saturated, subsequent spatial learning is impaired (McNaughton et al 1986;Castro et al 1989;Barnes et al 1994;Moser et al 1998). Barnes et al (1994) have shown that there is a correlation between the amount of LTP induced at these synapses and learning ability.…”
Section: Discussionmentioning
confidence: 99%
“…LTP induction has also been shown to have effects on spatial learning. Several groups have shown that when the perforant pathdentate synapses are saturated, subsequent spatial learning is impaired (McNaughton et al 1986;Castro et al 1989;Barnes et al 1994;Moser et al 1998). Barnes et al (1994) have shown that there is a correlation between the amount of LTP induced at these synapses and learning ability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that spatial learning is prevented when saturating LTP is evoked in the perforant pathway or when evoked by the repeated stimulation of a large number of hippocampal synaptic contacts (McNaughton et al, 1986;Casto et al, 1989;Moser et al, 1998;Dragoi et al, 2003). The effects of LTP evoked at the hippocampus are more evident for the acquisition of new learning skills and on recently acquired knowledge, but not for remote memory retrieval (Morris et al, 2003).…”
Section: General Remarksmentioning
confidence: 99%
“…Long-term potentiation (LTP) of neuronal synaptic responses has been discussed for 30 years as a possible model for synaptic changes that occur during learning (Lømo, 1966;Bliss and Lømo, 1973;McNaughton et al, 1986;Morris, 1989;Bliss and Collingridge, 1993). The standard protocol used by most researchers to induce LTP is high-frequency stimulation (HFS) in which several hundred pulses at frequencies of 100 -400 Hz are given to induce LTP.…”
mentioning
confidence: 99%